LOSS OF EPITHELIAL DUOX2 SIGNALING IS ACCOMPANIED BY A REDUCTION IN AKKERMANSIACEAE AND PROMOTES THE DEVELOPMENT OF METABOLIC SYNDROME IN A MICROBIOME-DEPENDENT MANNER. (26th January 2023) - Hazime, Hajar; Ducasa, Gloria; Brito, Nivis; Santander, Ana; Fernandez, Irina; Burgueno, Juan; Abreu, Maria
Abstract: BACKGROUND: Dysbiosis, an imbalance in microbial composition or function, is a key player in the development of conditions associated with chronic inflammation. The gut epithelium regulates host-microbiome dynamics through a variety of mechanisms, including the release of reactive oxygen species by NADPH oxidases. Dual oxidase 2 (DUOX2) is an antimicrobial NADPH oxidase expressed in the thyroid gland and gut epithelium and its activity is associated with dysbiosis. Loss of function mutations in DUOX2 are linked to the development of metabolic and inflammatory conditions such as congenital hypothyroidism and inflammatory bowel disease. Metabolic syndrome (MetS) is a cluster of conditions characterized by dysbiosis, inflammation, obesity, glucose intolerance, and hepatic steatosis. Dysbiosis in MetS is associated with a reduction in Bacteroidaceae and Akkermansiaceae. Despite this association, the mechanism by which dysbiosis leads to chronic inflammation and MetS is poorly defined. Here, we investigate the relationship between impaired epithelial barrier function and the development of MetS by focusing for the first time on intestinal specific DUOX2 deficiency as a mechanistic link. METHODS: Mice carrying an intestinal epithelial-specific deletion of DUOX2 (DA IEC-KO), and wild-type (WT) littermates were fed a standard diet and euthanized at 24 weeks. DUOX2 activity was determined by Amplex Red. Metabolic alterations were determined by glucose tolerance tests and body, adipose tissue, and liver weight measurements and histological and gene expression assessments. Intestinal permeability was determined by FITC-dextran and microbial translocation assessments. The role of the microbiome was assessed by RNA-sequencing of stool and in antibiotic-treated mice. RESULTS: DA IEC-KO mice produced less epithelial H2 O2 and exhibited increased body, liver, and adipose tissue weights that were accompanied by glucose intolerance and increased plasma triglycerides, lipid deposition in the liver, and lipid droplet size in adipocytes. Expression of macrophage and thermogenesis markers, F4/80, CD68, and UCP1 were altered in the liver and adipose tissue of these mice. DA IEC-KO mice showed altered gut permeability and increased bacterial translocation to the liver and adipocytes. Microbial sequencing revealed that loss of intestinal epithelial DUOX2 activity led to significant differences in alpha and beta diversity, and a marked reduction in the family Akkermansiaceae. Antibiotic depletion of the microbiota abrogated all MetS phenotypes observed. CONCLUSION: Our findings suggest that loss of intestinal epithelial DUOX2 activity leads to increased intestinal permeability and MetS in a microbiome dependent manner. These findings are significant in that they elucidate a novel role for epithelial DUOX2 at the host-microbial interface with distant systemic effects.